Perancangan Interior Pusat Kesehatan sebagai Sarana Edukasi untuk Anak di Surabaya - Gabriel Carmen Herriyanto; Mariana Wibowo (Intra, 2019)
Existence of Children medical Center with Educational Support are needed because psychological effects that influenced by design between children and adult are different. Many children do not take care of their healthy because of ignorance and wrong teaching methods which is most parents scared their children, therefore information about how to teach children to take care their own healthy is important. According to Shula Phonet content of design thinking are Inquiry, Emphatize, Define, Brainstorming, Prototype, Test, Apply and Reflect. Expected result of design of Children medical Center with Educational Supportis able to give a positif effect for children about healthy facilities and give children knowledge about how to take care their own healthy since early stage.